Yerba mate (Ilex paraguariensis, A. St.-Hil.) de novo transcriptome assembly based on tissue specific genomic expression profiles - Fay, Jessica Vannina (2018)
Fil: Fay, Jessica Vannina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico (Nordeste). Instituto de Biología Subtropical; Argentina.